2018
DOI: 10.1038/s41433-018-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of secondary intraocular lens implantation in children under 30 months of age

Abstract: PurposeTo report the long-term outcome of early secondary intraocular lens (IOL) implantation following congenital cataract extraction in a large number of eyes.MethodsData of aphakic children under 30 months of age who underwent secondary IOL implantation and had at least one year of follow-up after the surgery was reviewed. In all of the patients, a foldable three-piece acrylic IOL was implanted in the ciliary sulcus by the same surgeon using the same technique. The database studied included refractive and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…Although the safely of pediatric cataract surgery has improved, postoperative complications are still common in young children 5 because they are more prone to inflammatory reactions. The maintenance of a clear visual axis is important, particularly during the first 2-3 years of life, when children are more susceptible to amblyopia 18. The posterior capsule must be opened during surgery in young children to avoid this complication, and an anterior vitrectomy (AV) may be performed because the epithelial lens cells can also grow in the anterior vitreous.…”
Section: Discussionmentioning
confidence: 99%
“…Although the safely of pediatric cataract surgery has improved, postoperative complications are still common in young children 5 because they are more prone to inflammatory reactions. The maintenance of a clear visual axis is important, particularly during the first 2-3 years of life, when children are more susceptible to amblyopia 18. The posterior capsule must be opened during surgery in young children to avoid this complication, and an anterior vitrectomy (AV) may be performed because the epithelial lens cells can also grow in the anterior vitreous.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to greater inflammation, early cataract surgery increases the risk of glaucoma most likely due to disturbances in the angle and anterior segment, which are not yet well-formed in infants. Solebo et al and Koch et al (6,23) found more cases of glaucoma in children who had undergone surgery prior to 6 months of life and that a young age at the time of surgery was the only factor associated with glaucoma. Trivedi et al (9) showed that the risk of glaucoma was higher in aphakic and pseudophakic eyes of pacients who underwent cataract surgery <4.5 months than older patients.…”
Section: Discussionmentioning
confidence: 97%
“…Of these potentially relevant articles, 176 publications were excluded for various reasons, and 33 publications met the inclusion criteria and were included in this report. These comprised 3 RCTs [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] and 15 nonrandomized studies, [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] relevant to research questions 1, 2, 3, and 4. No economic evaluations relevant to research questions 5 and 6 were identified. There were 16 clinical publications and 1 methods publication (which was not included in the overall count) 77 that reported on the same RCT -the Infant Aphakia Treatment Study (IATS).…”
Section: Quantity Of Research Availablementioning
confidence: 99%
“…The RCTs were conducted in the US [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]77 and India. 60,61 The nonrandomized studies were conducted in the US, [63][64][65] Germany, 66 Ireland, 67,68 UK, 69 Latvia, 70 China, 71 India, [72][73][74] France, 75 Brazil, 62 and Korea. 76 There were multiple publications for the IATS, which were published in 2020, 46,50,53 2016, 55,56 2015, 52,59 2014, 45,49,58 2013, 54,57 2012, 51 2011, 47,48 and 2010.…”
Section: Study Characteristicsmentioning
confidence: 99%